宽闭锁系数多片式差速摩擦副研究 - 宁克焱; 韩明; 兰海 (Jixie chuandong)
The present situation of differential technology is introduced,and the process and main outcome of the wide locked coefficient multi-piece differential friction pair research are expatiated.With the differential friction-sliding mathematic model to 4×4 vehicle is found,the research on the complicated work condition to friction pair of differential mechanism locked friction is completed,and typical work condition of high performance vehicle differential friction and sliding is obtained.Based on the use and design require,the friction and abrasion characteristic parameters,as well as the testing method are defined.With the test under two kinds of lubricate condition,the friction and abrasion characteristics of many differential friction pair（includes 3 kinds of material and 11 test piece） are researched,the friction pair structure design,friction material research and lectotype direction,the load-add scheme strategy of the automatic friction differential are obtained,a friction pair theory model machine whose locked coefficient can be controlled between 0.1and 1.0 is formed.The technique foundation for achieving high performance vehicle differential is settled through the research.